2020
DOI: 10.4103/jpbs.jpbs_52_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of silver nanoparticles incorporated acrylic light cure resin trays

Abstract: A BSTRACT The conventional denture base resins had many drawbacks. Hence, the objective of this study was to compare the effect of incorporation of silver nanoparticles on mechanical properties of light-cured resin material. Materials and Methods: Specimens of acrylic resin (control group) and acrylic resin reinforced with 2% silver nanoparticles (test group) were evaluated for mechanical properties such as impact strength, transverse strength, modulus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…While denture base materials are vulnerable to water sorption and solubility, they can absorb or loose soluble components in the liquids, depending on their composition of saliva and this is the reason why the degradation occurs in materials leading to discoloration. [ 19 ] Color changes in denture base materials may be due to exposure to oral fluids, beverages, and denture cleaners. Color stability of provisional restoration using PMMA and bis-acrylic-based materials was evaluated by Gujjari et al ., and concluded that PMMA was more color stable than bis-acrylic composite-based resin using ultraviolet spectrophotometer.…”
Section: Discussionmentioning
confidence: 99%
“…While denture base materials are vulnerable to water sorption and solubility, they can absorb or loose soluble components in the liquids, depending on their composition of saliva and this is the reason why the degradation occurs in materials leading to discoloration. [ 19 ] Color changes in denture base materials may be due to exposure to oral fluids, beverages, and denture cleaners. Color stability of provisional restoration using PMMA and bis-acrylic-based materials was evaluated by Gujjari et al ., and concluded that PMMA was more color stable than bis-acrylic composite-based resin using ultraviolet spectrophotometer.…”
Section: Discussionmentioning
confidence: 99%
“…To address these two drawbacks, materials with strengthening features are added for the preparation of photocurable resin composites with directional properties. The incorporation of materials with strengthening features can fully leverage the synergistic effect of two or more materials, thereby reducing the shrinkage and enhancing the tensile strength of photocurable resin composites [3][4][5].…”
Section: Introductionmentioning
confidence: 99%